The Influence Of Green Marketing, Green Perceived Risk, Green Brand Image And Green Satisfaction On Consumer Loyalty Toward Avoskin Products - Aura Sabbrina; Annio Indah Lestari Nasution (LP2M IAIN Palopo, 2025)
Green marketing represents a managerial approach that aims to recognize, anticipate and meet the demands of consumers and society in a sustainable and financially profitable manner. When implemented effectively, green marketing strategies tend to foster stronger consumer loyalty. Conversely, inadequate applications can negatively impact customer engagement. This study seeks to examine how green: marketing, perceived risk, brand image, and satisfaction affect consumer loyalty. The study used a descriptive quantitative methodology, utilizing multiple linear regression analysis with the help of SPSS software. A total of 100 respondents were selected through the non-probability sampling method using purposive sampling. These findings show that the four green marketing variables, green perceived risk, green brand image, and green satisfaction have a positive and statistically significant effect on consumer loyalty to Avoskin products.